Pengelolaan Infografis pada Sosialisasi Program Beasiswa Pendidikan Magister Menuju Doktor untuk Sarjana Unggul (PMDSU) melalui Instagram @ristekdikti - Hayati, Setiyo (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Research based on infographic management on social media Instagram @ristekdikti which conveys information on the scholarship program "Masters to Doctoral Education for Excellent Bachelors (PMDSU) Kemenristekdikti Batch 3 2017. As part of the community education program, especially students. Through infographics in this program, it is hoped that it will make it easier to convey information and be able to attract students' interest in participating in the PMDSU Kemenristedikti scholarship program. This research uses an interpretive paradigm with a qualitative approach and descriptive research methods with case studies. Researchers collected complete information through in-depth interviews and observations, then the information was analyzed using the Triangulation analysis technique. This research aims to design and map the management of infographics for the socialization of the PMDSU scholarship program batch 3 in 2017 via Instagram @ristekdikti. The research results show that with proper infographic management in socializing the PMDSU scholarship program via Instagram @ristekdikti, interest in the PMDSU scholarship program can be increased. So it is hoped that through infographics the objectives of the PMDSU Kemenristekdikti program can be achieved.